Being bored: Heidegger on patience and melancholy - Hammer, Espen (British journal for the history of philosophy, 2004)
While boredom in the first part of "The Fundamental Concepts of Metaphysics" bears significant structural similarities to anxiety, as scrutinised in "Being and Time", argues that the former category is more attractive in that it largely avoids the ethically unacceptable implications of interpreting the meaning of time in terms of anxious being-towards-death. Drawing on Levinas's objections to Heidegger's privileging of resolute "Dasein" over affectivity and responsivity, considers boredom, as outlined by Heidegger, as a condition of possibility of being placed in a relationship of responsibility. (Quotes from original text)